Miniaturized Dual-Band Bandstop Filter Using Multilayered E-Shape Microstrip Structure - Raaed T. Hammed (Engineering and Technology Journal, 2016)
This paperpresents a new design technique to realize a miniaturized dual-band rejection filter based on the E-shape microstrip structure for multifunctional wireless communication systems. The filter is designed on a double layer substrate to achieve compact size. On the bottom layer, two E-shape microstrip structures are realized and coupled through a space gap,gc, to perform the specified dual-bandstop response. The filtering response of the two bandstops is improved using a top layer substrate employing a main linestub. The main line is a half wavelength hairpin resonator. These two filter circuits are capacitivley coupled using overlapping microstrip lines.To demonstrate the proposed design technique, a multi-band bandstop filter is developed with rejection frequenciesof 2.4 and 5.3 GHz Wireless local Area Network (WLAN). The filter is designed and simulated using the momentum simulator of theAdvanced Design System (ADS) software package. The resulting filter has two second-order bandstops with four transmission poles and provides two band rejectionsof 25 dB and 35 dB at 2.4 GHz and 5.3 GHz respectively. The filter circuit size is very small, being of the order of about 26 mm2 excluding the feeding ports.